Geometrical isomerism directed electrochemical sensing - Kottaichamy, Alagar Raja; Begum, Shabbah; Devendrachari, Mruthyunjayachar Chattanahalli; Bhat, Zahid Manzoor; Thimmappa, Ravikumar; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thotiyl, Musthafa Ottakam (Analytical Chemistry, 2020)
We report the independent role of isomerism of secondary sphere substituents over their nature, a factor often overlooked in molecular electrocatalysis pertaining to electrochemical sensing, by establishing that isomerism redefines the electronic structure at the catalytic reaction center via geometrical factors. UV-vis spectroscopy and X-ray photoelectron spectroscopy suggest that a substituent's isomerism in molecular catalysts conjoins molecular planarity and catalytic activation through competing field effects and resonance effects. As a classical example, we demonstrate the influence of isomerism of the -NO2 substituents for the electrocatalytic multi electron oxidation of As(III), a potentially important electrochemical pathway for water remediation and arsenic detection. The isomerism dependent oxidative activation of catalytic center leads to a nonprecious molecular catalyst capable for direct As(III) oxidation with an experimental detection limit close to WHO guidelines. This work opens up an unusual approach in analytical chemistry for developing various sensing platforms for challenging chemical and electrochemical reactions.

Unprecedented isomerism-activity relation in molecular electrocatalysis - Kottaichamy, Alagar Raja; Begum, Shabbah; Nazrulla, Mohammed Azeezulla; Dargily, Neethu Christudas; Devendrachari, Mruthyunjayachari Chattanahalli; Bhat, Zahid Manzoor; Thimmappa, Ravikumar; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thotiyl, Musthafa Ottakam (Journal of Physical Chemistry Letters, 2020)
The role of electrocatalysts in energy storage/conversion, biomedical and environmental sectors, green chemistry, and much more has generated enormous interest in comprehending their structure-activity relations. While targeting the surface-to-volume ratio, exposing reactive crystal planes and interfacial modifications are time-tested considerations for activating metallic catalysts; it is primarily by substitution in molecular electrocatalysts. This account draws the distinction between a substituent's chemical identity and isomerism, when regioisomerism of the -NO2 substituent is conferred at the ``alpha'' and ``beta'' positions on the macrocycle of cobalt phthalocyanines. Spectroscopic analysis and theoretical calculations establish that the beta isomer accumulates catalytically active intermediates via a cumulative influence of inductive and resonance effects. However, the field effect in the alpha isomer restricts this activation due to a vanishing resonance effect. The demonstration of the distinct role of isomerism in substituted molecular electrocatalysts for reactions ranging from energy conversion to biosensing highlights that isomerism of the substituents makes an independent contribution to electrocatalysis over its chemical identity.

Unprecedented energy storage in metal-organic complexes via constitutional isomerism - Kottaichamy, Alagar Raja; Deebansok, Siraprapha; Deng, Jie; Nazrulla, Mohammed Azeezulla; Zhu, Yachao; Bhat, Zahid Manzoor; Devendrachari, Mruthyunjayachari Chattanahalli; Vinod, Chathakudath Prabhakaran; Kotresh, Harish Makri Nimbegondi; Fontaine, Olivier; Thotiyl, Musthafa Ottakam (Chemical Science, 2023)
The essence of any electrochemical system is engraved in its electrical double layer (EDL), and we report its unprecedented reorganization by the structural isomerism of molecules, with a direct consequence on their energy storage capability. Electrochemical and spectroscopic analyses in combination with computational and modelling studies demonstrate that an attractive field-effect due to the molecule's structural-isomerism, in contrast to a repulsive field-effect, spatially screens the ion-ion coulombic repulsions in the EDL and reconfigures the local density of anions. In a laboratory-level prototype supercapacitor, those with beta-structural isomerism exhibit nearly 6-times elevated energy storage compared to the state-of-the-art electrodes, by delivering similar to 535 F g(-1) at 1 A g(-1) while maintaining high performance metrics even at a rate as high as 50 A g(-1). The elucidation of the decisive role of structural isomerism in reconfiguring the electrified interface represents a major step forward in understanding the electrodics of molecular platforms.